Meet the parents - Tenebaum, Nancy; Rosenthal, Jane 1959-; De Niro, Robert 1943-; Roach, Jay 1957-; Roach, Jay 1957- (Universal Studios, 2001)
Male nurse Greg Focker is poised to propose to his girlfriend Pam during a weekend stay at her parents's home. But here's the catch...he needs to ask her father first. Alas, the fur flies as Jack Byrnes, Pam's cat-crazy, ex-CIA father, played hysterically, takes an immediate dislike to her less-than-truthful beau. Greg's quest for approval gets seriously sidetracked as Murphy's Law takes over and a hilarious string of mishaps turns him into a master of disaster and total pariah in the eyes of the entire family?all except for his shell-shocked girlfriend, who can't believe she still loves her one-man wrecking crew.